The impact of text messaging and modern technological applications on linguistic proficiency - Al-Mansour, Waad Mansour; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
This study intends to illustrate the effect of text messaging and modern technological applications on the linguistic proficiency of individuals. It focused on introducing clear examples of the mistakes made by individuals while writing text messages. Here, some studies encouraged the use of text messages as it has many positive effects and other studies ensured that text messages have many negative effects. The study results indicated that using and understanding the shortened forms of SMS language has unique meanings depending on the group that it belongs to as it indicates the belonging of persons to a certain group and avoids the strangers. Therefore, SMS language is thought to be the "secret code of youth". There is a fact that abbreviations are used because of space restrictions and young adults try to use them.